1995
DOI: 10.1111/jon199552101
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Photon Emission Computed Tomography of the Brain in Acute Mania and Schizophrenia

Abstract: Single-photon emission computed tomography (SPECT) imaging with n-isopropyliodoamphetamine (IMP) was performed on 11 patients with bipolar mania, 21 acute schizophrenics, and 15 healthy control subjects. Subjects were evaluated with neuropsychological tests and psychiatric rating scales. SPECT brain studies were blindly evaluated to assess the degree of radiopharmaceutical uptake in three neuroanatomical regions of interest in each hemisphere. All the control subjects, 1 manic patient, and 1 schizophrenic pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 18 publications
4
38
0
4
Order By: Relevance
“…Although data in primary mania is limited, a number of functional imaging studies have demonstrated state-dependent focal abnormalities in cerebral blood flow/metabolism (AlMousawi et al, 1996;Blumberg et al, 2000;Blumberg et al, 1999;Goodwin et al, 1997;Gyulai et al, 1997;Migliorelli et al, 1993;Nobler et al, 1994;O'Connell et al, 1995;Rubin et al, 1995). Broadly consistent with the literature on secondary mania, altered temporal lobe activity has been reported in several functional imaging studies of primary mania.…”
Section: Maniamentioning
confidence: 71%
“…Although data in primary mania is limited, a number of functional imaging studies have demonstrated state-dependent focal abnormalities in cerebral blood flow/metabolism (AlMousawi et al, 1996;Blumberg et al, 2000;Blumberg et al, 1999;Goodwin et al, 1997;Gyulai et al, 1997;Migliorelli et al, 1993;Nobler et al, 1994;O'Connell et al, 1995;Rubin et al, 1995). Broadly consistent with the literature on secondary mania, altered temporal lobe activity has been reported in several functional imaging studies of primary mania.…”
Section: Maniamentioning
confidence: 71%
“…Both groups were compared with respect to executive functioning. Similar levels of cognitive impairment would be expected in mania and acute schizophrenia, since some overlapping has also been observed with respect to clinical symptomatology or neuroimaging findings in these states [4, 19, 24, 25], in spite of contradictions of several investigations [26, 27]. Nevertheless, less attention has been paid to the most extreme positions of the postulated common pathway between schizophrenia and bipolar disorder, such as remitted bipolar patients and negative schizophrenics.…”
Section: Methodsmentioning
confidence: 99%
“…However, after adjusting for hemispheric metabolism, which was also decreased in depression, the specific regional specificity in the striatum was less clear. O'Connell et al 72 reported increased blood flow in the basal ganglia, with right-sided flow greater than left, in bipolar patients during mania. Blumberg et al 64 partially replicated this finding as they observed increased blood flow in the left head of the caudate in manic compared with healthy subjects.…”
Section: Subcortical and Medial Temporal Activationmentioning
confidence: 99%